Cardiac Tamponade in Post-CABG Surgery Patient: A Case Report of Post-Pericardiotomy Syndrome - Lee, Jonathan Vincent; Emmanuela, Mirela; Lee, Jonathan Bryan; Damay, Vito Anggarino (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Background: Cardiac tamponade is the situation where fluid accumulates in the pericardial cavity and compresses the heart, which leads to reduced cardiac output and shock. Their prevalence in post-open heart surgery, especially Coronary Artery Bypass Graft (CABG) surgery is 24% and commonly related to Post-Pericardiotomy Syndrome (PPS). Case Summary: A 57-year-old female with a history of CABG surgery presented to emergency with chief complaints of shortness of breath in the last 3 days, especially when lying down. The patient underwent CABG surgery from CAD2VD + LM in the last month. Physical examination found a muffled first & second heart sound and distended jugular vein. The electrocardiograph of the patient showed sinus rhythm with low voltage. Echocardiography was done on the patient, and the result showed severe pericardial effusion with a D shape and collapse of the right ventricle. We performed a pericardiocentesis with an initial drainage of 737 cc of serosanguineous fluid. Post-procedural echocardiography showed reduced pericardial effusion, good LV contractility, and RV not collapsed. Pericardial fluid analysis concluded it was a transudative type. Patient were stable on admission and discharged uncomplicated. This patient developed cardiac tamponade with a history of CABG surgery. Conclusion: Cardiac tamponade occurs frequently in post-CABG surgery patients, both in early and late onset. It is important to recognize the early signs of cardiac tamponade, as the condition does not always present during the early phase. This case also highlighted the importance of recognizing and preventing PPS as a delayed cause of tamponade, even when there is no apparent sign of systemic inflammation. -- Highlight: 1. A 57-year-old post-CABG patient presented with cardiac tamponade one month after surgery, ultimately diagnosed as post-pericardiotomy syndrome (PPS) based on clinical and imaging findings. 2. Prompt echocardiography-guided pericardiocentesis and recognition of PPS as a delayed inflammatory cause of tamponade highlight the importance of vigilance for late-onset complications after cardiac surgery.